A study on the 3D printing technology and its future in the Arab world - Abdussalam Ali Ahmed , Khalleefah Majhoud Arhoumah, Abdullah Asmaeil, Salima Abukraa (Journal of Pure & Applied Sciences, 2019)
This paper aims to present a brief study of study of one of the modern methods of manufacturing, which is called 3D printing, which has become a prominent topic because of its great importance in the rapid development of manufacturing techniques. This paper discusses important topics about 3D printing, It gives some definitions and provides a brief overview about the development of the 3D- printing method . The most common methods of this technique are Selective laser sintering (SLS), Fused Deposition Modelling (FDM ), Photopolymerizatio. This paper also presents the most important materials used in the 3D printing technology such as ceramics, nylon, etc. The final section of this paper is an overview of the future of the 3D printing technology in Libya and the Arab world.